Clean Label “Rocha” Pear (Pyrus communis L.) Snack Containing Juice By-Products and Euglena gracilis Microalgae - Lomba-Viana, Xavier; Raymundo, Anabela; Prista, Catarina; Alegria, Maria João; Sousa, Isabel (Frontiers in Nutrition, 2022)
‘Rocha’ do Oeste pear is a Portuguese Protected Designation of Origin variety and one of the country's most relevant fruits for its nutritional value, production area, and exportation amounts. The recent integration of a pilot-scale juice production line brought to SUMOL+COMPAL company the need to characterize the new resulting fractions and value the new by-products. The objective of this work was to value the juice clarification by-products, producing a clean label and fiber-rich snack, in a circular economy rationale, where the secondary products are upcycled back into the food value chain, by creating another food product that includes those by-products. For the above to be possible, the laboratory conditions to produce pear fractions were optimized. After optimizing the puree centrifugation, using response surface methodology (RSM), and optimizing the turbid juice crossflow filtration, the different fractions were characterized in rheological, nutritional, and physical aspects. Comparison to the pulps revealed an increase in the viscosity of the pomace; an enriching effect on the fructose, glucose, and dietary fiber levels in the pomace, and maintenance of the vitamin C levels after centrifugation; and with no effect on the contents of total phenols during the filtration step. A thick pear snack was developed, incorporating retained fraction, inulin, and Euglena gracilis in the pomace, and optimized regarding its firmness and dietary fiber content. The snack characterization revealed an interesting total phenols content (which was maintained from the raw materials). Compared to the snack without microalgae and a commercial fruit snack, the pear snack with E. gracilis was well accepted by the sensory panel, mainly in texture and appearance, and can be further improved in aroma and flavor. The snack without microalgae was the favorite among the three samples, in most sensory parameters, and never got the answer "I'm sure I wouldn't buy it". Therefore, an innovative, clean label and plant-based snack was developed, in a circular economy rationale, which was relatively well appreciated by the panel. This snack is rich in dietary fiber, having the possibility of presenting various nutritional claims, and the potential for easy sensory optimization.